An other-typological illustration of the Exodus story according to Dr King"s perception of universal reconciliation in his sermon on Exodus 14:30 - Yang, Sunggu (HTS teologiese studies, 2016)
The article contends that Dr King makes an other-typological illustrative use of the Exodus story in his preaching – one of the most significant biblical narratives that the Black church in the US holds dear. This peculiar use of the Exodus story differentiates itself from the conventional typological understanding and use of the same story in the Black church’s history. While in the latter the Exodus story has a symbolic meaning of the irreconcilable conflict between the oppressed and the oppressing reality, in the former the same story contains a spiritual lesson that what is really hoped for in the midst of the seemingly irreconcilable racial and social conflict is compassion, liberation, and reconciliation for both parties involved. This article, by examining a representative sermon of Dr King on the Exodus story, shows that his other-typological illustrative approach originates from his fundamental theological ideal of universal reconciliation.